Acute insecticides mixture induced oxidative stress, DNA damage and nuclear abnormalities in three economically important freshwater species Catla catla, Cirrhina mrigala, and Labeo rohita - Naz, Huma; Abdullah, Sajid; Ahmed, Tanveer; Ur-Rehman, Najeeb; Ali, Basharat; Aziz, Kousar; Hassan, Muhammad Adeel; Zahid, Nimra; Saif, Warisha; Ahmad, Muhammad; Chaudary, Mahnoor; Iqbal, Rashid; et al. (Penerbit Universiti Kebangsaan Malaysia, 2025)
Insecticides are the most significant pollutants that negatively affect the aquatic ecosystem globally. They are extensively applied in various industries and agriculture to manage the pests and weeds. The freshwater ecosystems are especially vulnerable to these insecticides because insecticides enter into them through leaching, drifting, runoff and drainage. Insecticides can adversely affect the aquatic animals including fish. Therefore, the experiment was conducted to evaluate the acute toxic effect of bifenthrin(B), chlorpyrifos(C) and endosulfan(E) mixtures on antioxidant enzymes (SOD, CAT, Pox, and GST) activities and genotoxic potential in three fish species Cirrhina mrigala, Labeo rohita, and Catla catla exposed for 4 days. Results demonstrated that the CAT activity increased in gills (G), liver (L), and kidney (K) of three fish species exposed tertiary mixture while it was decreased in brain (B), heart (H) and muscle (M) of fish. Comparison among three fish species showed that there was minor difference among fish species for CAT activity. Exposure of insecticides mixture caused a significant increase in GST, POx, and SOD activities in all selected organs of three species of fish. GST activity was maximum in B of fish followed by the L, M, K, G, and H. The POx activity in organs of three fish species followed the trend: L>B>G>K>H>M. The SOD activity in organs of fish followed the trend: L>B>K>G>H>M. DNA damage in terms of micronuclei (MN), nuclear abnormalities (BN, DN, BLN, NN, and DEN), genetic damage index (GDI) and % damaged nuclei (DN) in peripheral erythrocytes of three fishes increased significantly as a result of pesticides exposure with increasing duration as 96>72>48>24-h. The highest damage in DNA (DN and GDI), NA and MN were observed in erythrocytes of C. catla followed by that of C. mrigala and L. rohita. As a conclusion, antioxidant activities and DNA damage of different fish species based on their physiological differences may be useful biomarker for evaluation of aquatic pollution.